An insights of Building Information Modelling (BIM) in facility management: case study of KKR2 Tower / Nafisah Mohd Mokhtar and Junainah Mohamad - Mohd Mokhtar, Nafisah; Mohamad, Junainah (2023)
Building Information Modelling (BIM) is defined as three dimensions (3D) technology that can represent an accurate virtual model of a building. BIM can be used for the designing and planning stage, the construction stage and the operation and maintenance stage. However, BIM used in FM remains limited. This has resulted, the stakeholder does not have the confidence to invest in BIM for managing the operation and maintenance stage of a building. Due to that, this research aims to investigate the level of BIM implementation on Facility Management in KKR2 Tower and to determine benefits of BIM implementation on Facility Management in KKR2 Tower. The research used a qualitative approach by conducting online interviews with the respondent. The finding of the research is based on PWD’s management toward the BIM model. The data analysis showed that the level of BIM implementation for handing over documents is already at Level 3 - the illustration of the building plan is provided in 2D and 3D, handing over the document is using the Jcloud server and the BIM model can be accessed by professional teams, client and PWD’s asset management. Meanwhile, the benefits of using BIM in Facility Management were agreed by the respondent; reduced cost of operation and maintenance, improved time response, improve documentation system, and enhance workers' productivity and efficiency.